Evaluating the Effects of Computer-Based Instruction on Trial-Based Functional Analyses Procedures. Issue 3 (May 2022) - Amador, Jessica L.; DeBar, Ruth M.; Sidener, Tina M.; Gardner, Andrew W.
Children who engage in problem behavior are often educated in the public schools. A trial-based functional analysis (TBFA) is an experimental functional analysis whereby conditions are embedded into scheduled activities of the school day to identify environmental variables responsible for problem behavior. To be included in this process, it is important that staff are trained effectively and efficiently. Computer-based instruction (CBI) offers several advantages as a staff training tool including less training time, less required supervision, and permits self-paced and individualized training. The efficacy of CBI on procedures of TBFA to practitioners remains unknown. We evaluated the efficacy of CBI teaching procedures of TBFA with 20 practitioners. Results indicate that CBI is an effective and efficient staff training procedure as post-test scores increased following the CBI training across participants with a mean training duration of less than an hour. Three practitioners successfully implemented four conditions of a TBFA with a confederate following CBI training. Following completion of the study, respondents ranked procedures of the CBI as socially valid.